Leishmaniosis ¿When to Hospitalize? - Pedro Navarro; Jorge Riera; Ana Carvajal; Silvya Silva; Luis Colmenares; Haydeé Ríos; Karla Romero; Virginia Coraspe; Marisela Silva; María Antonia De la Parte (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
Leishmaniasis is an endemic parasitic infectious disease of worldwide distribution. In Venezuela the main characteristics correspond to american tegumentary leishmaniasis (cutaneous l calized, cutaneous-mucous, cutaneous diffuse) and visceral leishmaniasis (kala azar). The localized cutaneous variety represents 90% of the cases attended at the ambulatory medical clinic for rural endemic diseases at the Tropical Medicine Institute, Pediatric and Adult services for Infectious Diseases at the Universitary Hospital of Caracas, and these patients are treated with pentavalent antimonials. In some clinical conditions hospitalization is required. We describe eight cases of patients treated under hospitalization. Case 1) a two year old girl with cutaneous leishmaniasis who had received immunotherapy for this parasitic disease; case 2) fifty nine year old female with nasal leishmaniasis; case 3) sixty four year old male with a rubber tapper's ulcer in the ear; case 4) thirty six year old male with treatment failure to pentavalent antimonials having received immunotherapy for leishmaniasis; case 5) fifty nine year old male alcoholic patient, with extended ulcer of five years evolution; case 6) eighty three year old female with cutaneous leishmaniasis in the legs; case 7) thirty three year old male with leishmaniasis of the nasal mucosa and AIDS; case 8) thirty seven year old male with kalaazar. We discuss the reasons for hospitalization and the dosage of pentavalent antimonials administered.